Effect of planting date and fertilization on Phaeosphaeria leaf blight in maize - Pegoraro, Diego Girardi; Vacaro, Elton; Nuss, Claudio Natalino; Soglio, Fábio Kessler dal; Sereno, Maria Jane Cruz de Melo; Neto, José Fernandes Barbosa (Pesquisa Agropecuaria Brasileira, 2001)
The increase of the area cultivated with maize in Brazil, together with some cultural practices, has favored the severity of Phaeosphaeria leaf spot, caused by Phaeosphaeria maydis. As a consequence, grain yield decreased, especially in areas with late planting and zero tillage. The present work was planned to evaluate the severity of P. maydis in six maize hybrids, in five planting dates and fertilized in two different levels. The experiment was sowed in Xanxerê, SC, Brazil, during the 1997/98 season. Plants were evaluated 30 days after flowering and percentage of damaged leaf area was registered. The results indicated that as planting date was delayed, there was an increase in disease severity and a decrease in grain yield. Levels of fertilization did not affect disease severity. The September planting date showed the lowest Phaeosphaeria leaf spot severity and the largest grain yield. There was a significant correlation (r = 0.45) between grain yield and severity of Phaeosphaeria maydis, indicating that the disease is an important factor to reduce grain yield.